Editorial - Pasierbek, Wit (Horyzonty Wychowania, 2017)
The concept of ethos, taking into account the frequency of itsusage, for instance in the debates of thinkers, politicians andmedia people, appears settled in our culture, language and consciousness.On the other hand, everyday day that we experiencerepeatedly seems to challenge this postulated omnipresence andsignificance of ethos. What does it prove?